Essential features of professional and pedagogical design - Литвиненко, О. В. (Pedagogy of Higher and Secondary Education, 2012)
Lytvynenko O. V. Essential features of professional and pedagogical design. It is told about the essence indifications of professionaly-pedagogical projection at the article. It has been defined the main stages and practical activities as for creation of pedagogical project, structurally-functional components of professionalypedagogical projection.